SPECTROSCOPIC CHARACTERIZATIONS OF ALPHA FETO PROTEINBINDING WITH ITS ANTIBODY BY IRMA METHOD IN TISSUE’SHOMOGENATE OF SOME TYPES OF OVARIAN TUMORS - Al Mudhaffar, Sami; Hasan, Hathama; Abu Al Temman, Nada (Iraqi Journal of Science, 2024)
Spectroscopic studies, in the ultraviolet region were carried out to characterize thebinding of isolated AFP with its labeled antibody in human malignant germ cell ovariantumor homogenates. Factors affecting the absorption properties of AFP, and the complexof isolated AFP with the labeled antibody such as pH, solvent polarity (solventperturbation technique), spectrophotometric pH titration and thermal stability in thepresence of different concentration of sodium chloride have been studied. Thespectroscopic pH titration curves for human AFP and for the complex of isolated AFPwith the labeled antibody gave pka of 5.7 and 7.3 for histidine residue, respectively,while 11.6 and 11.4 for tyrosine residue, respectively. Furthermore the study showedthat 23.8% of histidine and 70.4 % of tyrosine residue are located on the surface ofhuman AFP antigen, while these residues were located 38.0% and 31.0% on the surfaceof complex of the isolated AFP form.